Isolation, fractionation, identification and bioassay studies of the pheromone of the maconellicoccus hirsutus (green, 1908) - Deb, Mamata; Kumar, Dolly (International Journal of Biological Research, 2016)
Maconellicoccus hirsutus (Green, 1908) is one of the invasive pests known to infest the agricultural crops of Vadodara, Gujarat. Large amount of pesticides are in use to control this pest which ultimately pose threat to both environment and mankind. So eco-friendly measures are required to limit the invasion of this pest. Hence the objective is to isolate the pheromone from Maconellicoccus hirsutus to uncover its different components through GC-MS along with the bioassay studies. Pheromone was isolated from the species through adsorbent method, and the volatiles were then subjected to GC-MS for fractionation. Crude extracts was further employed for behavioral bioassay to identify the nature of the pheromone. Combined result of GC and GC-MS indicated the presence of phenolic component in the extract. Additionally, observations from bioassay studies confirmed it as sex pheromone where attractive index of males towards volatiles was higher (0.88) than the females. Hence, identification of different pheromonal components will be helpful in synthesizing chemical analogues and their use in controlling the concerned pest in an eco-friendly way.